Peran Kepala Asrama dalam Mengatasi Polarisasi Kesukuan Di Asrama Mahasiswa Institut Nalanda - Kamelia Metta Tirta; Ida Fitri Astuti; Ficky Firdiansha; Majaputera Karniawan (Advances In Education Journal, 2025)
This study began from the existence of friendship groups in the student dormitory that are often formed based on ethnicity or regional background. This condition can make relationships among residents less close and create social distance if not properly managed. A dormitory should be a place to learn to live together in diversity; therefore, the role of the dormitory head is very important in maintaining harmony within it. The purpose of this study is to understand how the dormitory head plays a role in overcoming ethnic differences at the Nalanda Institute Student Dormitory. The research used a descriptive qualitative method with three data collection techniques: (1) observation, by directly observing the activities and interactions of students in the dormitory; (2) interviews, conducted with the dormitory head and six students to explore their views about differences in the dormitory; and (3) document study, by reviewing documents related to dormitory life. The results show the dormitory head strives to foster harmony through various collective activities, utilizing two main strategies: educating students about the importance of cross-regional friendships and establishing collaborative multi-ethnic groups. The second strategy is considered more effective in practice because it is based on active social contact, which aligns with the principles of Saraniyadhamma in Buddhism and Allport's theory of intergroup interaction. At the student level, ethnic differences can be managed through open communication, cooperation, and strengthening the values ​​of togetherness in dormitory life.